2017
DOI: 10.11648/j.ijpbs.20170201.12
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Emotion Regulation Skills and Meta-cognitive Beliefs in Reducing Social Phobia Among Students- A Casual-Comparative Study

Abstract: Abstract:The purpose of this study was to compare the efficacy of emotion regulation skills and meta-cognitive beliefs in reducing social phobia among students. The study method was experimental type. The statistical society of this study was consisted of 60 high school girls in Tehran, who were selected randomly as case group and were divided evenly into three groups (each group 20 individuals). Emotion regulation and meta-cognition training were considered for both groups for 8 sessions and one group was sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…The translated version of this instrument has been previously used in numerous studies carried out in Iran. 20,21 In the present study, the reliability of the questionnaire was confirmed with a Cronbach α coefficient of 0.93.…”
Section: Methodssupporting
confidence: 71%
“…The translated version of this instrument has been previously used in numerous studies carried out in Iran. 20,21 In the present study, the reliability of the questionnaire was confirmed with a Cronbach α coefficient of 0.93.…”
Section: Methodssupporting
confidence: 71%